2022
DOI: 10.3390/ma15072470
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Microstructure, and Corrosion Characterization of Dissimilar Austenitic 316L and Duplex 2205 Stainless-Steel ATIG Welded Joints

Abstract: The present work analyzed the microstructure, mechanical, and corrosion properties of a dissimilar activated tungsten inert gas (ATIG) welded 2205 duplex stainless-steel (2205 DSS) plate and AISI 316L austenitic stainless steel (316L ASS) and compared them to conventional dissimilar welded tungsten inert gas (TIG). The mixing design method is a tool used to establish the optimal combined flux to achieve a full-penetrated weld bead in one single pass. A microstructure study was carried out by scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…in this. 47 Li et al 48 joined 301LN cold-rolled ASS to Q235B mild steel via the RSW process. They could find columnar dendrites (CD) including the martensite phase ( α ) as well as a low fraction of δ -ferrite phase and very tinny interdendritic (ID) austenite phase in the WM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in this. 47 Li et al 48 joined 301LN cold-rolled ASS to Q235B mild steel via the RSW process. They could find columnar dendrites (CD) including the martensite phase ( α ) as well as a low fraction of δ -ferrite phase and very tinny interdendritic (ID) austenite phase in the WM.…”
Section: Resultsmentioning
confidence: 99%
“…The microstructural analysis for WM could represent a ferritic-austenitic structure that mostly contained grain boundary, intergranular, and Widmansta¨tten austenite. 46 Touileb et al 47 analyzed inactivated and activated GTAW of AISI 316L/AISI 2205 DSS. They reported that the WM structure had a ferritic matrix with Widmansta¨tten needles, intragranular austenite, and allotriomorphic austenite in the grain boundary.…”
Section: Microstructural Characteristicsmentioning
confidence: 99%
“…Reinforcement corrosion is an important factor affecting the durability of reinforced concrete structures, and this poses a great threat to the safety of reinforced concrete (RC) structures [ 1 , 2 , 3 ]. Particularly, the corrosion in prestressed concrete bridge-beams provokes significant prestress losses, which induces cracking and excessive deflections during service conditions [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, an important issue has been the evaluation of proper filler metals for welds of Mo-rich stainless steels, such as the AISI 317L stainless steel, specified for critical applications in onshore and offshore oil and gas processing units, chemical and petrochemical plants, paper and pulp industries and other facilities.For that, an investigation of the filler metal chemical composition relation to the δ-ferrite amount and to the elemental partitioning in the weld metal and HAZ has been carried out to keep the corrosion and mechanical properties of the welded joint similar to the base metal. Recently, duplex stainless steels have been investigated as filler metal to weld Mo-rich austenitic stainless steels to mitigate metallurgical and mechanical problems that arise due to the secondary phases precipitations during welding of austenitic stainless steels [8][9][10][11][12][13] . However, no studies were found in the literature specifically regarding this application for the 317L steel.…”
Section: Introductionmentioning
confidence: 99%